High-durability fuel cell Pt alloy catalyst as well as preparation method and application thereof

Through solvent heat treatment and thermal reduction treatment, a high-durability fuel cell Pt alloy catalyst was prepared, which solved the problem of poor catalyst durability and achieved high activity and high stability catalyst performance.

CN119400877APending Publication Date: 2025-02-07HENAN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411537818.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The poor durability of existing fuel cell catalysts leads to prone to size growth, metal dissolution and activity losses in high temperatures and long-term operations, which seriously affects the stability and performance of the catalyst.

Method used

The high-durability fuel cell Pt alloy catalyst was prepared by platinum acetylacetonate, indium acetylacetonate and polyvinylpyrrolidone K30.

Benefits of technology

The PtIn3/C catalyst prepared by this method has high mass activity and electrochemically active area, and has excellent quad-electron selectivity and durability, and can maintain stable performance in high temperature and long-term operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400877A_ABST
    Figure CN119400877A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fuel cell catalysts, and particularly relates to a high-durability fuel cell Pt alloy catalyst and a preparation method and application thereof. The preparation method of the high-durability fuel cell Pt alloy catalyst comprises the following steps: (1) sequentially dispersing platinum acetylacetonate, indium acetylacetonate and polyvinylpyrrolidone K30 into a non-aqueous solvent, and carrying out solvent heat treatment; (2) after the solvent heat treatment is finished, cooling, carrying out solid-liquid separation, and washing and drying the obtained solid to obtain a Pt alloy catalyst intermediate; (3) mixing and grinding the Pt alloy catalyst intermediate and carbon black to obtain a solid mixture; and (4) carrying out thermal reduction treatment on the solid mixture. The invention develops a small-size Pt alloy catalyst with high activity and high durability, and the small-size Pt alloy catalyst not only has high quality activity and electrochemical active area, but also has very excellent four-electron selectivity and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cell catalysts, and in particular relates to a high-durability fuel cell Pt alloy catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen fuel cells have become an important direction for future energy decarbonization due to their advantages such as high efficiency, cleanliness and carbon-free. Catalysts are one of the core materials of fuel cells, accounting for more than 40% of the cost of fuel cell stacks, mainly at the cathode end of hydrogen fuel cells. A large amount of platinum (Pt)-based catalysts are required to catalyze the oxygen reduction reaction (ORR). However, platinum-based catalysts have low activity, poor durability, large dosage and high cost, which seriously hinder the large-scale industrialization of hydrogen fuel cells (Liang et al. Science 374, 6566 (2021).). Therefore, reducing the amount of Pt is a problem that must be solved in the development of hydrogen fuel cells. However, with the decrease of the platinum content in the catalyst layer, the voltage loss will inevitably increase, which will lead to poor hydrogen fuel cell performance from the efficiency point of view. In view of this, researchers have developed advanced Pt-based catalysts with smaller activation polarization voltage loss, because their higher mass activity can compensate for the voltage loss of low Pt cathodes in high potential areas (Liang et al. Nat Commun 14, 5896 (2023).). Reducing the size of the catalyst and constructing an ultrafine nano Pt-based catalyst with a high electrochemical active area (ECSA) is essential for providing sufficient catalytic sites while reducing the loading of Pt. However, ultrafine nanoparticles with a high surface area-to-volume ratio are thermodynamically metastable, and stability is difficult to meet requirements (Huang et al. Nat. Nanotechnol. 17, 968-975 (2022).), first, at high temperatures, due to the sharp increase in surface energy as the particle size decreases, metal nanoparticles have a strong tendency to sinter. Second, in long-term operation, significant size growth or metal dissolution is prone to occur, and this sintering, size growth, and metal dissolution will inevitably lead to the loss of active metal surface area, thereby causing catalyst deactivation (Yin et al. Nat Commun 12, 4865 (2021).).

[0003] The surface atomic structure and composition of the catalyst play a crucial role in the electrocatalytic performance of platinum-based catalysts (Wang et al. Adv. Sci. 7, 1901279 (2020).). Generally, the use of platinum is reduced by alloying Pt with transition metals such as Fe, Co, Ni, Cu and Mn (Pt-M). Compared with Pt / C catalysts, Pt-alloys, especially ordered intermetallic compounds, show significantly enhanced ORR activity and durability due to their more compressed unit cells and higher formation enthalpy (Wu et al. Proc. Natl. Acad. Sci. USA 118, e2104026118 (2021).). However, during the operation of acidic hydrogen fuel cells, the transition metal atoms in the Pt-M alloy catalyst will be rapidly leached due to oxidation, corrosion and Fenton reaction, resulting in the collapse of the catalyst skeleton, especially for catalysts with uneven particle size, which seriously damages their mass activity and ultimately reduces their lifespan. Therefore, achieving long-range stability of Pt alloy catalysts in hydrogen fuel cells faces very severe challenges, requiring that the design of nanocatalysts take into account both ultra-small catalyst size and excellent stability.

[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0005] The object of the present invention is to provide a high-durability fuel cell Pt alloy catalyst and a preparation method and application thereof, so as to help solve or improve the problem of poor durability of fuel cell catalysts.

[0006] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a method for preparing a high-durability fuel cell Pt alloy catalyst, comprising the following steps: (1) dispersing platinum acetylacetonate, indium acetylacetonate and polyvinylpyrrolidone K30 in a non-aqueous solvent in sequence and performing solvent thermal treatment; (2) after the solvent thermal treatment, cooling, solid-liquid separation, washing and drying the obtained solid to obtain a Pt alloy catalyst intermediate; (3) mixing and grinding the Pt alloy catalyst intermediate with carbon black to obtain a solid mixture; (4) performing thermal reduction treatment on the solid mixture to obtain the high-durability fuel cell Pt alloy catalyst.

[0007] Preferably, in step (4), the thermal reduction treatment is carried out in a mixed atmosphere of hydrogen and argon, the temperature of the thermal reduction treatment is 400-900° C., and the time of the thermal reduction treatment is 1-3 h.

[0008] Preferably, in the mixed atmosphere of hydrogen and argon, the volume fraction of hydrogen is 5%; and the heating rate during the thermal reduction treatment is 8-15° C. / min.

[0009] Preferably, in step (1), the temperature of the solvent thermal treatment is 150-220° C., and the time of the solvent thermal treatment is 5-10 h; the solvent thermal treatment is carried out in a high-pressure reactor; and the non-aqueous solvent is a volatile solvent selected from at least one of benzyl alcohol, acetaldehyde, toluene, ethanol and acetone.

[0010] Preferably, in step (1), the mass ratio of platinum acetylacetonate, indium acetylacetonate and polyvinylpyrrolidone K30 is (0.5-2):(1-6):30.

[0011] Preferably, in step (3), the mass ratio of the Pt alloy catalyst intermediate to carbon black is (1-2):(2-5).

[0012] Preferably, in step (2), after cooling to room temperature, washing is first performed with a mixed solvent of cyclohexane and ethanol, then washing is performed with an organic acid, then washing is performed with ultrapure water until the pH value of the supernatant is 7, and finally washing is performed with ethanol; in the mixed solvent of cyclohexane and ethanol, the volume ratio of cyclohexane to ethanol is 1:1; and the organic acid is glacial acetic acid.

[0013] The present invention also provides a high-durability fuel cell Pt alloy catalyst, which adopts the following technical scheme: a high-durability fuel cell Pt alloy catalyst, wherein the high-durability fuel cell Pt alloy catalyst is prepared by the method as described above.

[0014] The present invention also provides the use of the high-durability fuel cell Pt alloy catalyst as described above, which adopts the following technical solution: the use of the high-durability fuel cell Pt alloy catalyst as described above in the cathode end oxygen reduction reaction of a proton exchange membrane fuel cell.

[0015] The present invention also provides a fuel cell, which adopts the following technical solution: a fuel cell, wherein the fuel cell contains the high-durability fuel cell Pt alloy catalyst as described above.

[0016] Beneficial effects:

[0017] (1) The present invention provides a new approach to prepare ultrafine ordered Pt alloy catalysts. Compared with the traditional gas phase / liquid phase chemical method combined with high temperature (>900°C) heat treatment synthesis method, this method uses low melting point late transition metals and Pt alloying to avoid high temperature heat treatment, thereby preparing highly ordered PtIn3 alloy catalysts with an average particle size of about 3 nm. The preparation process is simple and easy to prepare in batches.

[0018] (2) The present invention mixes and grinds the Pt alloy catalyst intermediate with carbon black to make the alloy more evenly dispersed on the carbon carrier, which can achieve rapid refinement and activation of the alloy to a certain extent. Combined with thermal reduction treatment (low temperature), the metal-carrier interaction and the order of the alloy can be effectively improved. The preparation method is simple and easy to expand.

[0019] (3) The present invention uses low-melting-point and Fenton-free late transition metal In to alloy with Pt. The introduction of low-melting-point metal can improve the order of alloy nanoparticles; In does not have Fenton effect due to its fully occupied d orbital electronic structure, which can avoid the generation of active oxygen species during the reaction and reduce the oxidation and corrosion of the carrier and metal components; on the other hand, through the strong interaction of pd orbital hybridization, the dissolution and precipitation of alloy catalyst components are effectively suppressed, and a dual-site adsorption catalytic reaction mechanism is realized, thereby improving the intrinsic activity of the alloy catalyst. Therefore, the present invention has developed a small-sized PtIn3 / C catalyst with both high activity and high durability, which not only has high mass activity and electrochemical active area, but also has very excellent four-electron selectivity and durability. The present invention can help the large-scale industrialization of hydrogen fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0021] Figure 1 Middle: The left figure (a) is a transmission electron microscopy (TEM) image of the PtIn3 / C catalyst of Example 1, with a scale of 20 nm; the right figure (b) is a high-resolution transmission electron microscopy (HR-TEM) image of the PtIn3 / C catalyst of Example 1, with a scale of 5 nm.

[0022] Figure 2 X-ray diffraction (XRD) spectra of the PtIn3 / C catalyst prepared in Example 1 and the PtIn0 / C catalyst prepared in Comparative Example 1.

[0023] Figure 3 Middle: The left figure (a) is the linear sweep voltammetry (LSV) curves of the PtIn3 / C catalyst prepared in Example 1, the PtIn0 / C catalyst prepared in Comparative Example 1, the Pt3In / C catalyst prepared in Comparative Example 2 and the commercial Pt / C catalyst tested in an O2-saturated 0.1M HClO4 solution at 1600rpm; the right figure (b) is the mass activity (MA) and ECSA of the PtIn3 / C, PtIn0 / C and Pt / C catalysts.

[0024] Figure 4In the figure: Figure a shows the H2O2 yield and the number of transferred electrons of the PtIn3 / C catalyst prepared in Example 1, the PtIn0 / C catalyst prepared in Comparative Example 1, the Pt3In / C catalyst prepared in Comparative Example 2, and the commercial Pt / C catalyst; Figure b shows the LSV curve of the PtIn3 / C catalyst prepared in Example 1 before and after 100,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution; Figure c shows the LSV curve of the Pt3In / C catalyst prepared in Comparative Example 2 before and after 100,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution; Figure d shows the LSV curve of the PtIn0 / C catalyst prepared in Comparative Example 1 before and after 50,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution; Figure e shows the LSV curve of the commercial Pt / C catalyst before and after 50,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0026] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0027] The present invention aims at solving the problem of poor durability of existing fuel cell catalysts and provides a method for preparing a high-durability fuel cell Pt alloy catalyst.

[0028] The method for preparing a high-durability fuel cell Pt alloy catalyst of an embodiment of the present invention comprises the following steps: (1) dispersing platinum acetylacetonate, indium acetylacetonate and polyvinylpyrrolidone K30 in a non-aqueous solvent in sequence and performing solvent thermal treatment; (2) after the solvent thermal treatment, cooling, solid-liquid separation, washing and drying the obtained solid to obtain a Pt alloy catalyst intermediate; (3) mixing and grinding the Pt alloy catalyst intermediate with carbon black to obtain a solid mixture; (4) performing thermal reduction treatment on the solid mixture to obtain a high-durability fuel cell Pt alloy catalyst. Among them, polyvinyl pyrrolidone K30 is a surfactant that can control the shape and particle size of Pt alloy nanoparticles (size control is a key factor in optimizing the intrinsic activity of electrocatalysts); the residue (residual polyvinyl pyrrolidone K30) can be removed by centrifugation and washing in the later stage; in step (1), by performing solvent thermal treatment in a non-aqueous solvent, the non-aqueous solvent can better promote the alloying of metals with high melting points or high reduction energy barriers with Pt, and at the same time achieve a wide range of control over the components, sizes and morphologies of various Pt-based nanostructures, making it possible to construct fuel cell catalysts with low Pt content, high catalytic activity and high stability.

[0029] The preparation method of the high-durability fuel cell Pt alloy catalyst of the present invention adopts low-melting-point late transition metal In and Pt to alloy, avoids high-temperature heat treatment, improves the order of the alloy, and can prepare a highly ordered PtIn3 alloy catalyst with an average particle size of about 3nm; the Pt alloy catalyst intermediate is mixed with carbon black by a mixed grinding method, so that the alloy can be more evenly dispersed on the carbon carrier, and rapid refinement and activation of the alloy can be achieved to a certain extent. Combined with thermal reduction treatment, the metal-carrier interaction and the order of the alloy can be effectively improved, and the thermodynamic stability of the alloy catalyst can be improved; at the same time, In does not have a Fenton effect due to its fully occupied d orbital electronic structure, so the generation of active oxygen species can be avoided during the reaction, and the oxidation and corrosion of the carrier and metal components can be weakened; on the other hand, In and Pt interact strongly through pd orbital hybridization, effectively inhibiting the dissolution and precipitation of the alloy catalyst components, and realizing a dual-site adsorption catalytic reaction mechanism, thereby enhancing the durability while improving the intrinsic activity of the alloy catalyst. Therefore, the method of the present invention can prepare a small-sized high-durability fuel cell Pt alloy catalyst (i.e., PtIn3 / C catalyst) with both high activity and high durability, which not only has high mass activity and electrochemical active area, but also has very excellent four-electron selectivity and durability, and can be successfully applied to the ORR at the cathode end of hydrogen fuel cells. The synthetic raw materials used in the method of the present invention are widely available and low in price, which greatly reduces the cost of fuel cell catalysts.

[0030] The high-durability fuel cell Pt alloy catalyst prepared by the method of the present invention is helpful to solve or improve the problems of easy dissolution, low activity and poor durability of Pt alloy catalyst components in the prior art.

[0031] In a preferred embodiment of the method for preparing a high-durability fuel cell Pt alloy catalyst of the present invention, in step (4), the thermal reduction treatment is carried out in a mixed atmosphere of hydrogen and argon, the temperature of the thermal reduction treatment is 400-900°C (for example, 400°C, 500°C, 600°C, 700°C, 800°C or 900°C; preferably, the temperature of the thermal reduction treatment is 400-800°C; more preferably, the temperature of the thermal reduction treatment is 500-700°C; further preferably, the temperature of the thermal reduction treatment is 400-600°C), and the time of the thermal reduction treatment is 1-3h (for example, 1h, 1.5h, 2h, 2.5h or 3h; preferably, the time of the thermal reduction treatment is 1-2.5h; more preferably, the time of the thermal reduction treatment is 1-2h; further preferably, the time of the thermal reduction treatment is 1.5-2h). Among them, if the thermal reduction temperature is too low and the time is too short, the order of the Pt alloy is low, and the catalyst activity and stability are insufficient; if the temperature is too high and the time is too long, it will cause aging phenomenon, and small-sized particles will grow or agglomerate into large-sized particles, causing a significant decrease in intrinsic activity and mass activity.

[0032] In a preferred embodiment of the method for preparing a high-durability fuel cell Pt alloy catalyst of the present invention, in the mixed atmosphere of hydrogen and argon, the volume fraction of hydrogen is 5%; the heating rate during thermal reduction treatment is 8-15°C / min (for example, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min; preferably, the heating rate during thermal reduction treatment is 10-15°C / min; preferably, the heating rate during thermal reduction treatment is 8-12°C / min; more preferably, the heating rate during thermal reduction treatment is 12°C / min). Among them, if the heating rate is too low, the crystallinity is low; if the heating rate is too fast, the reaction is insufficient and even causes agglomeration, and higher requirements are also put forward for high-temperature furnace equipment (the maximum heating rate of a general high-temperature furnace is 15°C / min).

[0033] In a preferred embodiment of the method for preparing a high-durability fuel cell Pt alloy catalyst of the present invention, in step (1), the temperature of the solvent thermal treatment is 150-220°C (for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C), and the time of the solvent thermal treatment is 5-10h (for example, 5h, 6h, 7h, 8h, 9h or 10h); the solvent thermal treatment is carried out in a high-pressure reactor. If the temperature of the solvent thermal treatment is too low and the time is too short, the order of the Pt alloy is low, and the catalyst activity and stability are insufficient; if the temperature of the solvent thermal treatment is too high and the time is too long, it will cause a ripening phenomenon, and small-sized particles will grow or agglomerate into large-sized particles, causing a significant decrease in intrinsic activity and mass activity.

[0034] Preferably, the temperature of the solvent thermal treatment is 160-210°C (e.g., 165°C, 175°C, 185°C, 195°C or 205°C), and the time of the solvent thermal treatment is 6-9h (e.g., 6.5h, 7.5h or 8.5h); preferably, the temperature of the solvent thermal treatment is 160-200°C, and the time of the solvent thermal treatment is 6-10h; more preferably, the temperature of the solvent thermal treatment is 180-200°C (e.g., 183°C, 186°C, 189°C, 192°C or 197°C), and the time of the solvent thermal treatment is 7-8h (e.g., 7.2h, 7.4h, 7.6h, or 7.8h).

[0035] In a preferred embodiment of the method for preparing a high-durability fuel cell Pt alloy catalyst of the present invention, in step (1), the mass ratio of platinum acetylacetonate, indium acetylacetonate and polyvinyl pyrrolidone K30 is (0.5-2):(1-6):30 (for example, 0.5:1:30, 0.5:3:30, 0.5:6:30, 1:6:30 or 3:6:30). The usage ratio of platinum acetylacetonate, indium acetylacetonate and polyvinyl pyrrolidone K30 will have a significant impact on the catalytic effect of the prepared product; if the usage ratio of the three is not within the range specified by the present invention, the prepared product cannot achieve a catalytic effect equivalent to that of the product of the present invention.

[0036] Preferably, in (1), the mass ratio of platinum acetylacetonate, indium acetylacetonate and polyvinyl pyrrolidone K30 is (0.5-1.5):(2-5):30 (for example, 0.5:2:30, 0.5:5:30, 0.5:2.5:30, 1.5:2:30 or 1.2:2.5:30); more preferably, (1-1.2):(3-5):30 (for example, 1:4:30, 1.2:3:30, 1.2:5:30, 1.1:4:30 or 1.1:3:30); further preferably, the mass ratio of platinum acetylacetonate and indium acetylacetonate is 1:4-3:10, and the mass ratio of platinum acetylacetonate to polyvinyl pyrrolidone K30 is 1:30.

[0037] In a preferred embodiment of the method for preparing a high-durability fuel cell Pt alloy catalyst of the present invention, the non-aqueous solvent is a volatile solvent selected from at least one of benzyl alcohol, acetaldehyde, toluene, ethanol and acetone.

[0038] Preferably, the non-aqueous solvent is a mixed solvent of benzyl alcohol and acetaldehyde.

[0039] More preferably, in the mixed solvent of benzyl alcohol and acetaldehyde, the volume ratio of benzyl alcohol to acetaldehyde is 1:(1-2) (e.g., 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8 or 1:2); further preferably, in the mixed solvent of benzyl alcohol and acetaldehyde, the volume ratio of benzyl alcohol to acetaldehyde is 1:1.

[0040] In a preferred embodiment of the method for preparing a high-durability fuel cell Pt alloy catalyst of the present invention, in step (3), the mass ratio of the Pt alloy catalyst intermediate to carbon black is (1-2):(2-5) (for example, 1:2, 1:3, 1:5, 2:2, 2:3, 2:5 or 1.5:2.5; preferably, the mass ratio of the Pt alloy catalyst intermediate to carbon black is (1-1.5):(2-4); more preferably, the mass ratio of the Pt alloy catalyst intermediate to carbon black is (1.2-1.5):(2.4-3.5); further preferably, the mass ratio of the Pt alloy catalyst intermediate to carbon black is 1:(2-5)). The amount ratio of carbon black will affect the dispersibility of the prepared high-durability fuel cell Pt alloy catalyst.

[0041] Preferably, the mixed grinding method in step (3) is ball milling, and the ball milling time can be 1-3h (for example, 1h, 1.5h, 2h, 2.5h or 3h; preferably, the ball milling time can be 1-2.5h; more preferably, the ball milling time can be 1-2h).

[0042] In a preferred embodiment of the method for preparing a high-durability fuel cell Pt alloy catalyst of the present invention, in step (2), after cooling to room temperature, washing is first performed with a mixed solvent of cyclohexane and ethanol, then washing is performed with an organic acid, then washing is performed with ultrapure water until the pH value of the supernatant is 7, and finally washing is performed with ethanol; in the mixed solvent of cyclohexane and ethanol, the volume ratio of cyclohexane to ethanol is 1:1; and the organic acid is glacial acetic acid. Wherein, washing the solvent thermal product with a mixed solvent of cyclohexane and ethanol and an organic acid respectively helps to remove residual polyvinyl pyrrolidone K30.

[0043] Preferably, washing with a mixed solvent of cyclohexane and ethanol is performed 3-5 times (e.g., 3 times, 4 times or 5 times; preferably 4 times); after washing with a mixed solvent of cyclohexane and ethanol, the centrifugal speed is 10000-12000 rpm (e.g., 10000 rpm, 11000 rpm or 12000 rpm; preferably 10000-11500 rpm; more preferably 10500-11000 rpm), and the time of each centrifugation is 8-15 min (e.g., 8 min, 10 min, 12 min or 15 min; preferably 9-13 min; more preferably 10- 12min); washing with glacial acetic acid 2-4 times (for example, 2 times, 3 times or 4 times; preferably 3 times); the centrifugal speed is 10000-12000rpm (for example, 10000rpm, 11000rpm or 12000rpm; preferably 10000-11500rpm; more preferably 10500-11000rpm), and the time of each centrifugation is 10-20min (for example, 10min, 12min, 14min, 16min, 18min or 20min; preferably 10-18min; more preferably 12-16min).

[0044] In a preferred embodiment of the method for preparing a fuel cell Pt alloy catalyst of the present invention, in step (2), the drying method is freeze drying. Preferably, the freeze drying temperature is -60 to -40°C (e.g., -40°C, -45°C, -50°C, -55°C or -60°C), and the freeze drying time is 24-48h (e.g., 24h, 30h, 36h, 42h or 48h; the freeze drying time is preferably 26-45h; the freeze drying time is more preferably 30-40h).

[0045] The present invention also proposes a Pt alloy catalyst for a fuel cell. The Pt alloy catalyst for a fuel cell in an embodiment of the present invention is prepared by the method described above (PtIn3 / C catalyst).

[0046] The present invention also proposes the use of the above-mentioned Pt alloy catalyst for fuel cells, and the use of the above-mentioned Pt alloy catalyst for fuel cells in the cathode end oxygen reduction reaction of proton exchange membrane fuel cells.

[0047] The present invention also provides a fuel cell. The fuel cell according to an embodiment of the present invention contains the high-durability fuel cell Pt alloy catalyst as described above.

[0048] Preferably, the fuel cell is a proton exchange membrane fuel cell.

[0049] The high-durability fuel cell Pt alloy catalyst of the present invention and its preparation method and application are described in detail below through specific examples.

[0050] The reagents used in the following examples are all commercially available; the sources of some reagents are as follows: platinum acetylacetonate (98%), indium acetylacetonate (98%) and polyvinylpyrrolidone K30 (analytical grade) were purchased from Beijing Inokai Technology Co., Ltd., benzyl alcohol, acetaldehyde and glacial acetic acid were purchased from MacLean Biochemical Technology Co., Ltd., carbon black (Vulcan XC-72), commercial Pt / C (20%, Johnson Matthey).

[0051] Example 1

[0052] The preparation method of the high-durability fuel cell Pt alloy catalyst of this embodiment comprises the following steps:

[0053] (1) Platinum acetylacetonate (0.02 g), indium acetylacetonate (0.1 g) and polyvinylpyrrolidone K30 (0.6 g) were dispersed in turn into a mixed solution of 30 mL of benzyl alcohol and acetaldehyde (15 mL each) and magnetically stirred for 1.5 h to form a light yellow solution;

[0054] (2) The light yellow solution was transferred to a high pressure reactor and treated by solvothermal method at 180°C for 8 h;

[0055] (3) After the solvothermal reaction is completed, the mixture is naturally cooled to room temperature, and the solid is separated from the liquid to obtain a solid, which is then centrifuged and washed three times with the first solvent (a mixed solvent of cyclohexane and ethanol mixed in a volume ratio of 1:1), each time for 10 minutes and at a centrifugal speed of 11,000 rpm; then, glacial acetic acid is used for centrifugal washing three times, each time for 15 minutes and at a centrifugal speed of 11,000 rpm; finally, the mixture is washed with ultrapure water until the pH value of the supernatant is 7, and then the residual organic matter is washed with ethanol to obtain a precipitate; the precipitate is freeze-dried at -60 to -40°C for 40 hours to obtain a Pt alloy catalyst intermediate;

[0056] (4) The Pt alloy catalyst intermediate (0.01 g) and commercial carbon black (0.03) were mixed and ball-milled for 2 h to obtain a solid mixture;

[0057] (5) Then, the solid mixture is placed in a tubular furnace, introduced into a 5% H2 / Ar reducing atmosphere and subjected to thermal reduction treatment at 500°C at a heating rate of 10°C / min for 2 hours to obtain the high-durability fuel cell Pt alloy catalyst of this embodiment (small-sized ordered high-quality active and durable PtIn3 / C alloy catalyst).

[0058] Example 2

[0059] The preparation method of the high-durability fuel cell Pt alloy catalyst of this embodiment comprises the following steps:

[0060] (1) Platinum acetylacetonate (0.03 g), indium acetylacetonate (0.1 g) and polyvinylpyrrolidone K30 (0.9 g) were dispersed in 30 mL of a mixed solution of benzyl alcohol and acetaldehyde (15 mL each) and magnetically stirred for 2 h to form a light yellow solution;

[0061] (2) The light yellow solution was transferred to a high pressure reactor and treated by solvothermal method at 200°C for 10 h;

[0062] (3) After the solvothermal reaction is completed, the mixture is naturally cooled to room temperature, and the solid is separated from the liquid to obtain a solid, which is then centrifuged and washed four times with the first solvent (a mixed solvent of cyclohexane and ethanol mixed in a volume ratio of 1:1), each time for 12 minutes and at a centrifugal speed of 11,000 rpm; then, glacial acetic acid is used for centrifugal washing four times, each time for 15 minutes and at a centrifugal speed of 10,000 rpm; finally, the mixture is washed with ultrapure water until the pH value of the supernatant is 7, and then the residual organic matter is washed with ethanol to obtain a precipitate; the precipitate is freeze-dried at -60 to -40°C for 48 hours to obtain a Pt alloy catalyst intermediate;

[0063] (4) The Pt alloy catalyst intermediate (0.01 g) and commercial carbon black (0.02 g) were mixed and ball-milled for 3 h to obtain a solid mixture;

[0064] (5) The solid mixture is then placed in a tubular furnace, introduced into a 5% H2 / Ar reducing atmosphere and subjected to thermal reduction treatment at a temperature of 600°C at a heating rate of 12°C / min for 1.5 hours to obtain the high-durability fuel cell Pt alloy catalyst of this embodiment (small-sized ordered high-quality active and durable PtIn3 / C alloy catalyst).

[0065] Example 3

[0066] The preparation method of the high-durability fuel cell Pt alloy catalyst of this embodiment comprises the following steps:

[0067] (1) Platinum acetylacetonate (0.02 g), indium acetylacetonate (0.08 g) and polyvinylpyrrolidone K30 (0.6 g) were dispersed in 30 mL of a mixed solution of benzyl alcohol and acetaldehyde (15 mL each) and magnetically stirred for 1 h to form a light yellow solution;

[0068] (2) The light yellow solution was transferred to a high pressure reactor and treated by solvothermal method at 160°C for 6 h;

[0069] (3) After the solvothermal reaction is completed, the mixture is naturally cooled to room temperature, and the solid is separated from the liquid to obtain a solid, which is then centrifuged and washed three times with the first solvent (a mixed solvent of cyclohexane and ethanol mixed in a volume ratio of 1:1), each time for 8 minutes and at a centrifugal speed of 10,000 rpm; then, glacial acetic acid is used for centrifugal washing twice, each time for 12 minutes and at a centrifugal speed of 10,000 rpm; finally, the mixture is washed with ultrapure water until the pH value of the supernatant is 7, and then the residual organic matter is washed with ethanol to obtain a precipitate; the precipitate is freeze-dried at -60 to -40°C for 35 hours to obtain a Pt alloy catalyst intermediate;

[0070] (4) The Pt alloy catalyst intermediate (0.01 g) and commercial carbon black (0.05 g) were mixed and ball-milled for 1.5 h to obtain a solid mixture;

[0071] (5) The solid mixture is then placed in a tubular furnace, introduced into a 5% H2 / Ar reducing atmosphere and subjected to thermal reduction treatment at a heating rate of 8°C / min to 400°C for 1.5 hours to obtain the high-durability fuel cell Pt alloy catalyst of this embodiment (small-sized ordered high-quality active and durable PtIn3 / C alloy catalyst).

[0072] Comparative Example 1

[0073] The difference between Comparative Example 1 and Example 1 is that: indium acetylacetonate is not added in Comparative Example 1; the rest is consistent with Example 1.

[0074] Comparative Example 1 prepared PtIn0 / C catalyst.

[0075] Comparative Example 2

[0076] The difference between Comparative Example 2 and Example 1 is that the amount of platinum acetylacetonate used in Comparative Example 2 is 0.06 g; the rest is consistent with Example 1.

[0077] Comparative Example 2 prepared a Pt3In / C catalyst.

[0078] Experimental example

[0079] 1. Transmission electron microscope test:

[0080] Transmission electron microscopy characterization (TEM) was carried out on a Tecnai G220 transmission electron microscope from FEI, USA, with an accelerating voltage of 200 kV. Sample preparation method: First, grind the sample to be tested evenly with a mortar until no particles are present, then take a small amount of the ground sample powder to be tested and add it to ultrapure water or anhydrous ethanol, ultrasonicate for 20-30 minutes until it is evenly dispersed, take an appropriate amount of liquid and drop it onto the carbon support film or microgrid or copper mesh, and dry it at low temperature in a vacuum drying oven for testing.

[0081] The test results are as follows Figure 1 shown. Figure 1 The transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HR-TEM) images of the PtIn3 / C catalyst prepared in Example 1 have scale bars of 20 nm and 5 nm, respectively.

[0082] Figure 1 The characterization results show that: with the assistance of polyvinyl pyrrolidone K30, a PtIn3 / C alloy nanocatalyst with an average particle size of about 3 nm was prepared by solvent thermal chemical method combined with secondary low-temperature reduction treatment, which is beneficial to improving the mass activity and electrochemical active area; and the alloy has a high degree of order.

[0083] 2. X-ray diffraction:

[0084] X-ray photoelectron spectroscopy (XPS) is mainly used to detect and analyze the valence state and electronic structure of samples. XPS is performed on the ESCALAB 250Xi instrument of Thermo Fisher in the United States, using a focused monochromatic AlKα line (1486.6eV) X-ray beam with a diameter of 200μm. Charge correction is performed using C1s=284.80eV binding energy as the standard. Sample preparation method: tablet by tablet press or evenly apply the powder sample to the conductive tape.

[0085] Figure 2 The X-ray diffraction (XRD) spectra of the PtIn3 / C catalyst prepared in Example 1 and the PtIn0 / C catalyst prepared in Comparative Example 1.

[0086] Figure 2 The XRD characterization results show that the ordered PtIn3 / C catalyst is successfully obtained by the preparation method of the present invention, which is beneficial to inhibit the dissolution of alloy components and improve the stability of the catalyst; the comparison sample obtained without adding In source is a Pt / C catalyst.

[0087] 3. Oxygen reduction reaction test:

[0088] Test method: The oxygen reduction reaction test adopts a three-electrode test system, that is, a platinum mesh is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, and a glassy carbon electrode is used as a working electrode. Specifically, the catalyst prepared in Example 1 and Comparative Examples 1-2 and commercial Pt / C materials are prepared into slurry and loaded onto a glassy carbon electrode. Specifically, the method for experimentally loading the catalyst slurry onto a glassy carbon electrode is: take 2.0 mg of the catalyst sample, and disperse it at low temperature and ultrasonically in a solution prepared by 336.0 μL of ethanol, 144.0 μL of deionized water and 20 μL of Nafion 117 (~5%); after the prepared solution is ultrasonically mixed for 1 hour, 5.0 μL of the mixed solution is measured with a pipette, and vertically dripped on the glassy carbon electrode. After drying with an infrared lamp, it can be used as a working electrode; wherein the steps for preparing Example 1, Comparative Example 1, Comparative Example 2 and the commercial Pt / C working electrode are the same.

[0089] Test results:

[0090] Figure 3 LSV curves (a), MA and ECSA (b) at 1600 rpm of the PtIn3 / C catalyst prepared in Example 1, the PtIn0 / C catalyst prepared in Comparative Example 1, the Pt3In / C catalyst prepared in Comparative Example 2 and the commercial Pt / C catalyst tested in an O2-saturated 0.1M HClO4 solution.

[0091] Figure 3 The oxygen reduction activity test results show that the small-sized ordered PtIn3 / C (E 1 / 2 =0.901V) catalyst has significantly better ORR catalytic activity than PtIn0 / C (E 1 / 2 =0.812V) and the Pt3In / C catalyst prepared in Comparative Example 2 (E 1 / 2 =0.876V) and commercial Pt / C (E 1 / 2 =0.835V), where the MA of the PtIn3 / C catalyst is approximately 8 and 7 times that of the PtIn0 / C catalyst and commercial Pt / C, respectively, and the ECSA of the PtIn3 / C catalyst is approximately 9 and 5 times that of the PtIn0 / C catalyst and commercial Pt / C, respectively.

[0092] 4. Oxygen reduction reaction selectivity and durability test:

[0093] The selectivity of oxygen reduction reaction was tested by using a rotating ring disk electrode as the working electrode and linear sweep voltammetry. The durability test was performed by cyclic voltammetry with a test potential window range of 0.6-1.0 V vs. RHE and a scan rate of 50 mV s -1After the cycle is completed, the activity decay can be obtained by comparing the test LSV curve with the LSV curve before the cycle to analyze the durability of the catalyst.

[0094] Figure 4 In the figure, a is the test results of H2O2 yield and number of transferred electrons of the PtIn3 / C catalyst prepared in Example 1, the PtIn0 / C catalyst prepared in Comparative Example 1, the Pt3In / C catalyst prepared in Comparative Example 2 and the commercial Pt / C catalyst; b is the LSV curve of the PtIn3 / C catalyst prepared in Example 1 before and after 100,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution; c is the LSV curve of the Pt3In / C catalyst prepared in Comparative Example 2 before and after 100,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution; d is the LSV curve of the PtIn0 / C catalyst prepared in Comparative Example 1 before and after 50,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution; e is the LSV curve of the commercial Pt / C catalyst before and after 50,000 accelerated cycles in an O2-saturated 0.1M HClO4 solution.

[0095] Figure 4 The results of oxygen reduction reaction selectivity and durability test show that PtIn3 / C catalyst has lower H2O2 yield (<2%) and electron transfer closer to 4 in a wide potential window, which is better than PtIn0 / C, Pt3In / C catalyst and commercial Pt / C, proving that PtIn3 / C catalyst has higher four-electron selectivity; at the same time, PtIn3 / C catalyst has excellent durability. After 100,000 cycles of accelerated durability test, the half-wave potential (E 1 / 2 ) only dropped by 4 mV. After 100,000 cycles of accelerated durability test, the Pt3In / C catalyst 1 / 2 The PtIn0 / C catalyst and the commercial Pt / C catalyst showed a decrease of 30 mV after 50,000 cycles of accelerated durability test. 1 / 2 Drops of 39mV and 88mV respectively.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-durability fuel cell Pt alloy catalyst, characterized in that: The steps include: (1) dispersing platinum acetylacetonate, indium acetylacetonate and polyvinyl pyrrolidone K30 in a non-aqueous solvent in sequence and performing a solvent thermal treatment; (2) After the solvent thermal treatment is completed, cooling, solid-liquid separation, washing and drying the obtained solid to obtain a Pt alloy catalyst intermediate; (3) mixing and grinding the Pt alloy catalyst intermediate and carbon black to obtain a solid mixture; (4) The solid mixture is subjected to thermal reduction treatment to obtain the high-durability fuel cell Pt alloy catalyst.

2. The method for preparing a high-durability fuel cell Pt alloy catalyst according to claim 1, characterized in that: In step (4), the thermal reduction treatment is carried out in a mixed atmosphere of hydrogen and argon, the temperature of the thermal reduction treatment is 400-900° C., and the time of the thermal reduction treatment is 1-3 hours.

3. The method for preparing a high-durability fuel cell Pt alloy catalyst according to claim 2, characterized in that: In the mixed atmosphere of hydrogen and argon, the volume fraction of hydrogen is 5%; The heating rate during the thermal reduction treatment is 8-15°C / min.

4. The method for preparing a high-durability fuel cell Pt alloy catalyst according to claim 1, characterized in that: In step (1), the temperature of the solvent thermal treatment is 150-220° C., and the time of the solvent thermal treatment is 5-10 h; The solvent thermal treatment is carried out in a high pressure reactor; The non-aqueous solvent is a volatile solvent selected from at least one of benzyl alcohol, acetaldehyde, toluene, ethanol and acetone.

5. The method for preparing a high-durability fuel cell Pt alloy catalyst according to claim 1, characterized in that: In step (1), the mass ratio of platinum acetylacetonate, indium acetylacetonate and polyvinylpyrrolidone K30 is (0.5-2):(1-6):

30.

6. The method for preparing a high-durability fuel cell Pt alloy catalyst according to claim 1, characterized in that: In step (3), the mass ratio of the Pt alloy catalyst intermediate to carbon black is (1-2):(2-5).

7. The method for preparing a high-durability fuel cell Pt alloy catalyst according to claim 1, characterized in that: In step (2), after cooling to room temperature, washing is first performed with a mixed solvent of cyclohexane and ethanol, then washing is performed with an organic acid, then washing is performed with ultrapure water until the pH value of the supernatant is 7, and finally washing is performed with ethanol; In the mixed solvent of cyclohexane and ethanol, the volume ratio of cyclohexane to ethanol is 1:1; The organic acid is glacial acetic acid.

8. A high-durability fuel cell Pt alloy catalyst, characterized in that: The high-durability fuel cell Pt alloy catalyst is prepared by the method according to any one of claims 1 to 7.

9. Use of the high-durability fuel cell Pt alloy catalyst as claimed in claim 8 in the cathode end oxygen reduction reaction of a proton exchange membrane fuel cell.

10. A fuel cell, characterized in that: The fuel cell contains the high-durability fuel cell Pt alloy catalyst according to claim 8.